Hemodynamic Patterns Before Inhospital Cardiac Arrest in Critically Ill Children: An Exploratory Study. (14th June 2021) - Erez, Ely; Mazwi, Mjaye L.; Marquez, Alexandra M.; Moga, Michael-Alice; Eytan, Danny
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To characterize prearrest hemodynamic trajectories of children suffering inhospital cardiac arrest. DESIGN: Exploratory retrospective analysis of arterial blood pressure and electrocardiogram waveforms. SETTING: PICU and cardiac critical care unit in a tertiary-care children's hospital. PATIENTS: Twenty-seven children with invasive blood pressure monitoring who suffered a total of 31 inhospital cardiac arrest events between June 2017 and June 2019. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We assessed changes in cardiac output, systemic vascular resistance, stroke volume, and heart rate derived from arterial blood pressure waveforms using three previously described estimation methods. We observed substantial prearrest drops in cardiac output (population median declines of 65–84% depending on estimation method) in all patients in the 10 minutes preceding inhospital cardiac arrest. Most patients' mean arterial blood pressure also decreased, but this was not universal. We identified three hemodynamic patterns preceding inhospital cardiac arrest: subacute pulseless arrest ( n = 18), acute pulseless arrest ( n = 7), and bradycardic arrest ( n = 6). Acute pulseless arrest events decompensated within seconds, whereas bradycardic and subacute pulseless arrest events deteriorated over several minutes. In the subacute and acute pulseless arrest groups, decreases in cardiac output were primarily due to declines in stroke volume, whereas in the bradycardic group, the decreases were primarily due to declines in heart rate. CONCLUSIONS: Critically ill children exhibit distinct physiologic behaviors prior to inhospital cardiac arrest. All events showed substantial declines in cardiac output shortly before inhospital cardiac arrest. We describe three distinct prearrest patterns with varying rates of decline and varying contributions of heart rate and stroke volume changes to the fall in cardiac output. Our findings suggest that monitoring changes in arterial blood pressure waveform-derived heart rate, pulse pressure, cardiac output, and systemic vascular resistance estimates could improve early detection of inhospital cardiac arrest by up to several minutes. Further study is necessary to verify the patterns witnessed in our cohort as a step toward patient rather than provider-centered definitions of inhospital cardiac arrest.